Avena sativa’s Therapeutic Potential: Exploring Antiasthmatic Effects in Guinea Pig Asthma Model - Yerragopu, Anil Kumar; Anusha, V. L.; Aslam, Shaik; Rajesh, A.; Sirisha, Y.; Harini, A. L.; Ali, Shaik Faizan (Toxicology International, 2024)
Avena sativa (oat) has emerged as a potential therapeutic candidate for asthma, a global health challenge characterized by chronic airway inflammation. This research investigates the anti-asthmatic potential of the Hydro-Alcoholic Extract of Avena sativa (HAEAS) in a guinea pig asthma model induced by histamine and ovalbumin. The study explores the influence of HAEAS on oxidative stress markers, leucocytes, eosinophils, and histopathological changes in lung tissues. Results reveal that HAEAS, particularly at 400 mg/kg, significantly increases the latent period and percentage protection in histamine induced bronchospasm. In ovalbumin-sensitized guinea pigs, HAEAS demonstrates a notable reduction in total leucocyte count, eosinophils, neutrophils, and macrophages in bronchoalveolar lavage fluid. Moreover, HAEAS exhibits antioxidative effects by increasing superoxide dismutase levels and decreasing malondialdehyde levels. Histopathological analysis demonstrates a decrease in inflammatory cell infiltration, hyperplasia, and bronchoconstriction. This study highlights the potential of Avena sativa as a novel therapeutic avenue for asthma, offering anti-inflammatory and antioxidant benefits.